Qualitative and quantitative morphological indices of damage and reparation in idiopathic femoral head osteonecrosis in adults - V. V. Hryhorovskyi; О. E. Nirshberg (Zaporozhye State Medical University, 2014)
Aim. Idiopathic aseptic femoral head osteonecrosis is one of the diseases which happen often and in most cases lead to permanent disability. Methods and results. On purpose to establish qualitative-quantitative features and differences between pathomorphological changes and their consequences in comparison groups divided by lesion remoteness, on histotopogfaphic specimens of 30 femoral heads from patients with aseptic osteonecrosis values of parametric and nonparametric indices were investigated. Conclusion. It was found that aseptic femoral head osteonecrosis is large-focal lesion which persist for years and in overwhelming majority of cases does not lead to complete necrosis replacement. Statistically estimated intergroup differences of some morphological indices of femoral head tissue lesion and reparation indicate that pathological changes gradually progress in the direction of coxarthrosis of average or high degree.